2015
DOI: 10.1038/srep11819
|View full text |Cite
|
Sign up to set email alerts
|

Heat-Denatured Lysozyme Inactivates Murine Norovirus as a Surrogate Human Norovirus

Abstract: Human norovirus infects humans through the consumption of contaminated food, contact with the excrement or vomit of an infected person, and through airborne droplets that scatter the virus through the air. Being highly infectious and highly viable in the environment, inactivation of the norovirus requires a highly effective inactivating agent. In this study, we have discovered the thermal denaturing capacity of a lysozyme with known antimicrobial activity against gram-positive bacteria, as well as its inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Previous studies have confirmed that MNV-1 decreases by 4.5 log PFU/mL after exposure to heat-denatured lysozyme solution at 1 14) . Further, a sufficient inactivation effect was obtained with 1 heat-denatured lysozyme in vegetable salads 21) .…”
Section: Treatment Of Mnv-1 In Bread Fillings With Heat-de-mentioning
confidence: 68%
See 3 more Smart Citations
“…Previous studies have confirmed that MNV-1 decreases by 4.5 log PFU/mL after exposure to heat-denatured lysozyme solution at 1 14) . Further, a sufficient inactivation effect was obtained with 1 heat-denatured lysozyme in vegetable salads 21) .…”
Section: Treatment Of Mnv-1 In Bread Fillings With Heat-de-mentioning
confidence: 68%
“…Heat-denatured lysozyme was prepared as previously described 14) . Egg-white lysozyme (Kewpie Corporation, Tokyo, Japan) was dissolved in distilled water at a concentration of 5 (w/v, pH 6.5±0.2) and filtered using a 0.20 μm filter.…”
Section: Treatment Of Mnv-1 In Bread Fillings With Heat-denatured Lysmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanisms behind Aβ uptake is not known to date, but several receptors are believed to be implicated [239]. The reason for the decreased uptake could therefore be due to Aβ having an impaired ability to bind to the receptors when lysozyme is was previously reported that lysozyme has properties that goes beyond its enzyme activity, since inactivated lysozyme still possesses antimicrobial activity as well as the ability to neutralize murine norovirus [241]. Hence, lysozyme in itself could be important through other potential mechanisms than enzymatic activity.…”
Section: Lysozyme Prevents Aβ Toxicity Via Attenuation Of Aβ Uptakementioning
confidence: 99%